Bridging Firm's Innovation, Productivity and Export: An Analysis using Swedish CIS data - Viroj Jienwatcharamongkhol; Mohammad Hossein Tavassoli (European Regional Science Association (ERSA), 2012)
This paper analyses the effect of innovation on the well-established productivity-export association in the literature. Here, we argue that actively innovative firms have a higher productivity, which make them more likely to become exporters. Moreover, exporting firms learn from their trading experiences and accumulate the necessary knowledge in order to innovate further, which may facilitate future productivity. We use the micro-data from two waves of Swedish Community Innovation Survey (CIS) to provide empirical evidences to test our argument concerning this interrelation between innovation, productivity, and export. The main finding is that firms which become innovative are more likely to also become an exporter, especially when they do not have prior export experiences.
Keywords: D22; D24; F14; O39; 330; innovation; productivity; export; Swedish CIS; micro-data